The Bologna Process of German’s Media and Communication Studies - Yoseph Bambang Wiratmojo (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
Internationalization of the higher education system through the Bologna Process in German’s media and communication studies is on progress; all higher education institutions were chosen as the samples in this research had the same opinion that international student’s mobility in term of the Bologna Process was the most important variable to create international cooperation with other universities. Providing more courses in English also became their main concern to attract international students come their academic life. The implementation of the new curricula model, bachelor and masters, was considered more transparent and clearer in the structure and content than the Diplom and Magister models. Nevertheless, the compatible and comparable qualification principle of bachelor and masters structure brought also dilemma that some of the content of media and communication studies had to be adjusted considering the workload and study period that is different from the old curricula systems. The bachelor and masters structure caused apprehension that the bachelor graduates would prefer to work in industries than return to campus to pursue higher degree. This research was based on content analysis of curricula documents and interview transcription of some representative of HEI in media and communication studies.